MOORING LINE PRE-LAY AND INSTALLATION PROCEDURE - Mutadi, Mutadi (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2023)
Abstract. Mooring Line Pre -Lay and Installation Procedure is using AHTS with the power engine 30.000 BHP and has capacity of bollard pull 300 ton is used for mooring line installation for FPSO Marlin Natuna. The Mooring Installation often fail due to the anchor drag during testing. In this site activity the anchor drag is used. The type of anchor drage is strevpris MK6 with the weight 15 ton and after installation it should be test loaded 243 ton, it is 80% from his capacity 304 ton. The Acceptance criteria for the mooring installation is the anchor can not allow drage out of the target box, with allowable drage 13-16 m, during tension test with 30 minute the holding time. The result from the site activity of the mooring line installation as follow ; the tension mooring line number 1,2,3,4,5,6,7,8 are pass with the tension test 250 ton, and the final position of all anchor within in the target box eith the maximum drag 2m.